2020
DOI: 10.1002/cbin.11333
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of SNHG16 induced by CTCF accelerates cardiac hypertrophy by targeting miR‐182‐5p/IGF1 axis

Abstract: Long non‐coding RNA (lncRNA) SNHG16 has been reported to be significant regulators in multiple cancers. However, never has the relationship between it and cardiac hypertrophy been studied until now. In this study, angiotensin II (Ang II)‐treated cardiomyocytes isolated from neonatal mice were used as a model of cardiac hypertrophy in vitro. Real‐time quantitative polymerase chain reaction was performed to measure the expression of SNHG16, miR‐182‐5p, and insulin‐like growth factor 1 (IGF1). The relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The most important findings of our study were that, after we knocked down SNHG6 expression in HiPSC, the downregulation pattern of SNHG6 can be maintained until cardiac differentiation and we were able to show the rescuing effects of SNHG6 downregulation on PPFinduced cytotoxicity in HiPSC-CMs. Within the superfamily of SNHG lncRNAs, newly emerged evidence suggested that, other members than SNHG6, such as SNHG1 and SNHG16 are also actively involved in the development and pathology of cardiomyocytes (31,32). Our preliminary data also showed gene expression changes of other SNHG super-family than SNHG6 (data not shown).…”
Section: Discussionmentioning
confidence: 53%
“…The most important findings of our study were that, after we knocked down SNHG6 expression in HiPSC, the downregulation pattern of SNHG6 can be maintained until cardiac differentiation and we were able to show the rescuing effects of SNHG6 downregulation on PPFinduced cytotoxicity in HiPSC-CMs. Within the superfamily of SNHG lncRNAs, newly emerged evidence suggested that, other members than SNHG6, such as SNHG1 and SNHG16 are also actively involved in the development and pathology of cardiomyocytes (31,32). Our preliminary data also showed gene expression changes of other SNHG super-family than SNHG6 (data not shown).…”
Section: Discussionmentioning
confidence: 53%
“…miR-182-5p can prevent cardiac hypertrophy by regulating angiogenesis [ 32 , 33 ] and overexpressed miR-182-5p weakens the tube formation potential of vascular endothelial cells [ 34 ]. Our results revealed a similar expression pattern of miR-182-5p in the umbilical vein endothelial cells (HUVECs) and myocardial cells (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study indicates that silenced SNHG16 represses Ang II-imposed cardiac hypertrophy ( 18 ). In the present study, SNHG16 was upregulated in myocardial I/R injury and inhibition of SNHG16 could significantly improve I/R damage.…”
Section: Discussionmentioning
confidence: 96%